Prototyping for physical and digital products - McElroy, Kathryn (O'Reilly Media, 2016)
Prototyping and user testing is the best way to create successful products, but many designers skip this important step and use gut instinct instead. By explaining the goals behind prototyping-and demonstrating how to prototype for both physical and digital products-this O'Reilly report helps beginning and intermediate designers become more comfortable with creating and testing prototypes early and often in the process. Prototyping is a necessary skill in all areas of design, especially for startups, entrepreneurs, in-house designers, and freelancers. Author Kathryn McElroy explains various prototyping methods, from fast and dirty to high fidelity and refined, and reveals ways to test your prototypes with users. You'll gain valuable insights for improving your product, whether it's a smartphone app or a new electronic gadget. Understand what prototyping is, and why it's important to prototype early and often Know which fidelity level is needed for each different prototype Learn the similarities and differences between prototyping for physical and digital products Get best practices for prototyping with any medium, and choose which prototyping software to use Learn the basics of electronics prototyping and the resources for getting started Write basic pseudocode and understand how to translate it into usable code Conduct basic user tests to gain insights from prototypes to improve their product.